Application of Edible Coating by Carboxymethyl Cellulose, Chitosan, Konjac Glucomannan and Their Synergistic Effect on Storage of Mango (Mangifera Indica) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Mango (Mangifera indica) is a tropical fruit that has economic importance in Central Highland of Vietnam. It has good nutritional values such as vitamins, carotenoids, polyphenols, fibers and antioxidants. Mango fruit is very perishable and considerable postharvest quality defect is occurred due to ripening and senescence. Major obstacles of mango during preservation and shipping are weight loss, ripening, and formation of brown spots resulting in decreasing of its value. Mango is very susceptible to chilling injury. The use of the edible coating materials for prolonging shelf-life of mango is essential. The present study aimed to identify the effect of carboxymethyl cellulose (CMC), chitosan, CMC + glucomannan, chitosan + glucomannan as edible coating in storage of mango fruits. Results demonstrated that 0.5% chitosan: 0.25% konjac glucomannan as edible coating could be used to coating mango fruit and maintaining its shelf life to 15 days.Keywords: Mango, CMC, Chitosan, Glucomannan, Coating, shelf-life.